IMPLEMENTATION OF THE NEXT GENERATION SOCIAL WELFARE INFORMATION SYSTEM (SIKS-NG) IN SEKARDANGAN VILLAGE, SIDOARJO DISTRICT - Ningrum, Bella Tri Inda; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to find out about the Implementation of the Next Generation Social Welfare Information System (SIKS-NG) as a form of digital governance in Sekardangan Village, Sidoarjo District. Method: The method used is a descriptive qualitative method with interview techniques with application operators, field observations, and documentation studies in the form of archives, reports, and related administrative data. And data analysis developed by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawn. Results:  The results of the study show that the implementation of SIKS-NG in Sekardangan Village is going relatively well. However, there are still obstacles in several indicators according to Edward III: external communication is not optimal due to lack of official socialization, the disposition of implementers has not been maximized due to appointments without formal selection and the absence of special incentives, as well as bureaucratic structures that have not been supported by written SOPs despite the lack of fragmentation to make data consistent with the center. Novelty:  The novelty of this research lies in the analysis of the implementation of SIKS-NG at the village level using the framework of Edward III's theory comprehensively. This study presents a combination of results between the advantages and disadvantages of each indicator, as well as providing a contextual picture of e-government practices at the local level.